Neonatal Near Miss among Newborns of Women with Type 1 Diabetes Mellitus - Luiza R. Morais; Beatriz C. Patz; Felipe F. Campanharo; Patricia M. Dualib; Sue Y. Sun; Rosiane Mattar (Obstetrics and Gynecology International)
Objective. To investigate the frequency of neonatal near miss (NNM) and associate it with maternal morbidity in newborns of women with type 1 diabetes mellitus (T1DM). Methods. This was a cross-sectional retrospective study from a secondary analysis of data retrieved from medical records of pregnant women with T1DM cared at a Brazilian university hospital between 2005 and 2015. Maternal near miss (MNM) and potentially life-threatening conditions (PTLC) were classified according to the World Health Organization criteria. NNM was classified according to the Pan American Health Organization Neonatal Near Miss Working Group criteria. Association of maternal morbidity with NNM was assessed using chi-square test. Results. There were 122 newborns (NB) among 137 T1DM pregnancies. Thirty-seven NB presented NNM—incidence of 303 NNM per 1000 live births (37/122). NNM was associated with MNM (P<0.001, OR (95% CI): 17.15 (1.85–159.12)). PLTC did not increase the odds of NNM (P=0.07; OR (95% CI): 2.1281 (0.92–4.91)). Seven newborns died, six of them from pregnancies without severe maternal morbidity. 71% of the neonatal death (5/7) occurred in malformed neonates. Conclusion. MNM was associated with NNM among women with T1DM, and PLTC, paradoxically, did not increase NNM.